A seasonal regime-switching spot price model for the Philippine electricity market - Ibanez, Sebastian C.; Valdez, Adrian Roy L. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The aim of this paper is to present a mathematical model that caputres the unique spot price dynamics of the Philippine Wholesale Electricity Spot Market (WESM). We construct a three-state regime-switching model and employ a seasonal clustering algorithm to construct a "seasonal" model that captures the potential periodic patterns in the frequency of spikes. We also examine two important regulations, the primary and secondary price caps, and add their effects to our price simulations. Finally, a comparison of forecasting performance is made between the original model, its seasonal variant, and a simpler model consisting of 24 AR(1) processes.
Thesis (M.S. Computer Science)--University of the Philippines Diliman
Keywords: Electric utilities -- Rates -- Mathematical models; Spot prices -- Philippines